Secrecy outage analysis of double shadowed Rician channels. Issue 13 (1st June 2019) - Ai, Y.; Kong, L.; Cheffena, M.
Abstract : The double shadowed Rician model was recently proposed to describe some realistic physical signal propagation phenomena, where a Rician faded signal is impacted by cascaded shadowing processes. In this Letter, the authors study the outage performance of the double shadowed Rician model. More specifically, they investigate the impact of two different shadowing processes on the secrecy performance by deriving novel and exact expressions for secrecy outage performance metrics. The obtained results reveal the following physical implications: (i) when a Rician faded signal undergoes line‐of‐sight shadowing, which is further cascaded by another round of composite shadowing, the latter form of shadowing imposes larger impact on the secrecy performance; (ii) the widely investigated concept of 'protected zone' to improve the secrecy performance should not be limited to the legitimate transmitter but also extended to the legitimate receiver due to the adverse shadowing effect caused by objects in its vicinity; and (iii) the rate of outage performance degradation grows larger as the shadowings become severe.